Análisis de la aplicación de los principios de finalidad y consentimiento en la Ley de Protección de Datos Personales - Gordón Tafur, María Augusta (2024)
This degree work addresses the implementation of the principles of purpose and consent in the Personal Data Protection Law in Ecuador. The general objective of the study is to evaluate the adequacy and application of these principles in various entities, both public and private. The research faces the problem of guaranteeing ethical and secure management of information, respecting individual rights in the context of data protection. The applied methodology involves conducting interviews with key representatives of public and private entities such as: Coop. Atuntaqui, Electric Company of Ibarra EMENORTE, SENECYT, Comercial Hidrobo S.A. COMHIDROBO and the company DINARDAP. Qualitative methods were employed to obtain detailed insights into the implementation of the principles, using semi-structured interview techniques. The selected sample provides a diverse and representative perspective of the application of legislation in different sectors. The results highlight that there is widespread knowledge of the principles, however, challenges persist in their practical application, such as the lack of reliability in the information collected and difficulties in obtaining informed consent. Through the interviews carried out, specific cases of possible breaches of the principles were revealed, which may result in claims from affected users and possible sanctions by the competent data protection authorities. Finally, the sanctions established in the legislation will be established, highlighting the importance of rigorously complying with legal requirements on data protection to avoid adverse consequences, such as financial fines and damage to the reputation of organizations